2016
DOI: 10.1088/1752-7155/10/4/047101
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 3-pentanone under inflammatory conditions

Abstract: Breath analysis of rats using multi-capillary column ion-mobility spectrometry (MCC-IMS) revealed alterations in acetone and other ketones, including 3-pentanone, during inflammation. The alterations seem likely to result from oxidative branched-chain keto acid (BCKA) catabolism. We therefore tested the hypothesis that 3-pentanone arises during inflammation from increased BCKA oxidation in the liver with consequent accumulation of propionyl-CoA and its condensation products. Male Sprague-Dawley rats were anaes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…For example, 2-ethylhexanoic acid has been shown to be metabolized into 2-heptanone and 4-heptanone [23], and 2-pentanone is proposed to be formed via β-oxidation of hexanoic acid in the peroxisomal pathway [24]. Moreover, 3pentanone is also hypothesized to be produced via the oxidation of branched-chain keto acids [13]. More specifically, it is a product of the oxidative decarboxylation of 2-methyl-3-ketovaleric acid.…”
Section: Volatiles Produced and Metabolized By Ags Snu-1 And Ges-1 Ce...mentioning
confidence: 99%
“…For example, 2-ethylhexanoic acid has been shown to be metabolized into 2-heptanone and 4-heptanone [23], and 2-pentanone is proposed to be formed via β-oxidation of hexanoic acid in the peroxisomal pathway [24]. Moreover, 3pentanone is also hypothesized to be produced via the oxidation of branched-chain keto acids [13]. More specifically, it is a product of the oxidative decarboxylation of 2-methyl-3-ketovaleric acid.…”
Section: Volatiles Produced and Metabolized By Ags Snu-1 And Ges-1 Ce...mentioning
confidence: 99%
“…Five of the VOCs detected, 2-pentanone, 2-octanone, 3,7-dimethyl-decane, 2,5,6-trimethyl-decane and 2,2,6-trimethyl-octane, have previously been reported in human breath samples [4, 6, 52, 53]; the fact that they are expressed differentially between males and females is likely due to different physiological states. Ketones and methylated hydrocarbons related to those reported in this study have been implicated in altered metabolic states [5, 6, 39, 44]. Although animals were on the same diet at the time of the breath collection, differences in nutrient utilization and social behaviors have the potential to impact metabolite output.…”
Section: Discussionmentioning
confidence: 90%
“…Quantifying VOCs yields signatures, which may indicate the metabolic state of the organism. VOCs, which are present in all bodily fluids [4], can be products of cellular metabolism [3, 5]. An intriguing aspect of VOC research is the potential to identify disease status by comparing samples from disease and non-disease states.…”
Section: Introductionmentioning
confidence: 99%
“…L-valine belongs to the branched-chain amino acid (BCAA) family which plays an important role in brain function. Previous studies showed that the levels of BCAA metabolites were enhanced as inflammatory conditions persisted (Kleber et al, 2016). Moreover, the expression of IL-10 was increased in microglial cells in response to a high concentration of BCAA (De Simone et al, 2013).…”
Section: Discussionmentioning
confidence: 99%